Effect of environment enrichment to aggressive behaviour in piglets - Juhás, Peter; Vavrišinová, Klára; Hozáková, Katarina; Janíček, Martin; Debrecéni, Ondrej (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2020)
Aim of the paper was to evaluate the effect of various types of environment enrichment to aggressive behavior in piglets. Two types of pen were involved in tests - the pen with concrete floor cowered by straw (CFS) and the pen with slatted floor (SF). The CFS pen was enriched by temporary dividing to two parts by barrier with gap stuffed by straw (CFSD). Barrier was placed to the pen before shifting and mingling litters, two litters were placed each to another side. The gap was cleared from straw by the piglets during the pen exploration and mingling was unforced. The SF pen was enriched by plastic tube (SFT), PET bottle (SFB) and with anise smell (SFS). The number of attacks during 1st hour after shifting (NA1H) and total number of attacks during 8 hours after shifting to the new pen (TNA) and mean of attacks per 20 minutes intervals (MA20) have been evaluated. The CFSD modification significantly decreased MA20 (P < 0.001), TNA and NA1H were decreased too, difference was not significant. Modifications of SF pen had no significant effect. SFT led to decrease NA1H, TNA and MA20 were increased. SFS and SFB led to increasing all evaluated traits. The most effective seem to be space modification (CFSD). Moreover, Spearman correlation showed importance of space allocation per piglet. Higher space allowance leads to decrease of aggressive behavior -area per pig negatively correlated with NA1H (-4.19, P > 0.05), TNA and MA20 (ρ = -0.636, P < 0.05).